Human toxocariosis: in vitro production of soluble mediators against Toxocara canis infection - Marini, Vanina Natalia (2016)
Toxocara canis (T. canis) is an intestinal nematode that affects dogs. In humans, this geohelminth induces visceral larva migrans (VLM) syndrome, which is associated with eosinophilia, increased serum IgE and inflammation of the airways. In general, chronic nematode infections induce a polarized TH2 immune response.There are observations that the macrophages response to gastrointestinal nematodes in which the alternative activation pathway plays a more important role in resistance. However, whether or not Toxocara infectionsinduce alternative activation of human monocytes/macrophages is still a matter of debate. The objective of this study was to determine the pattern of IL12 and IL10 levels and nitric oxide (NO) production in vitro of human adherent cells against antigens from T. canis. For this purpose the in vitro cytokine production of adherent cells from healthy subjects was examined in response to stimulation with antigens from larval stage of T. canis.Cell culture supernatants were removed from antigen stimulated and unstimulated cultures after 24 hours, 15 and 20 days post infection and the concentration of IL-12, IL-10 and NO concentrations were determined.The results revealed high levels of IL-12 at 24 hours post stimulation. After that time, the concentration of this cytoquine declined to undetectable levels. IL-10 revealed a progressive increase from the 24 hours until the 20th day post stimulation. Conversely not detectable levels of NO were found during the study. Therefore,we concluded that during early T. canis infection, the activation and suppression of immune processes occur simultaneously and cytokines of adherent cells contribute to the regulation of the immune response.